Models Relating Individual Tree Basal Area Growth Rates to Tree Basal Areas in Even-Aged, Monoculture Forest Stands - West, PW; Ratkowsky, DA (Journal of Forests, 2022)
As trees grow larger in even-aged, monoculture forests, stand density increases, taller trees shade smaller trees and a group of smaller, suppressed trees develops that may show little or no growth. Subsequent mortality is most common from this group. This work compares three models that may describe well the relationship between individual tree basal area growth rates and tree basal areas in a forest stand when a suppressed group of trees is present or not. The models are tested using a large collection of data from permanent sample plots in blackbutt (Eucalyptus pilularis Smith) forests in subtropical eastern Australia. An example is given for one stand showing how model parameter values may change as the stand ages; this illustrates how these models have potential for use in the first stage of model development to relate individual tree growth rates to tree sizes and stand characteristics. Such models may then be used widely across the forest population under consideration.